2008
DOI: 10.1103/physrevb.78.115424
|View full text |Cite
|
Sign up to set email alerts
|

In situneutron diffraction study of adsorbed carbon dioxide in a nanoporous material: Monitoring the adsorption mechanism and the structural characteristics of the confined phase

Abstract: The behavior of molecules confined in a nanoporous material was studied by adsorption from the gas phase with in situ neutron diffraction, with the aid of a high-pressure adsorption apparatus and the General Materials diffractometer ͑GEM, ISIS͒. The aim of this work is to establish the combined adsorption/neutron diffraction technique as a unique tool to elucidate both the adsorption mechanism and the structure of molecules confined in nanoporous materials. For this reason, a well-defined mesoporous system ͑MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…22,23 Earlier studies that combined CO 2 sorption (at various thermodynamic states) and total neutron scattering on ordered mesoporous materials (MCM-41, SBA-15, CMK-3) have revealed the structural details of pore-confined CO 2 . [24][25][26][27] Surprisingly, it was also observed that during freezing SBA-15 and CMK-3 samples loaded with CO 2 below the bulk critical point, the confined CO 2 molecules did not freeze or remain liquid as expected, but escaped from the pores. 26,27 Moreover, when the total scattering data are combined with atomistic Monte Carlo simulations, detailed information concerning the accurate positions of the confined fluids within the pores can be extracted.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…22,23 Earlier studies that combined CO 2 sorption (at various thermodynamic states) and total neutron scattering on ordered mesoporous materials (MCM-41, SBA-15, CMK-3) have revealed the structural details of pore-confined CO 2 . [24][25][26][27] Surprisingly, it was also observed that during freezing SBA-15 and CMK-3 samples loaded with CO 2 below the bulk critical point, the confined CO 2 molecules did not freeze or remain liquid as expected, but escaped from the pores. 26,27 Moreover, when the total scattering data are combined with atomistic Monte Carlo simulations, detailed information concerning the accurate positions of the confined fluids within the pores can be extracted.…”
Section: Introductionmentioning
confidence: 79%
“…The evaluated total structure factor of pore-confined CO 2 is proportional to the absolutely calibrated differential cross section obtained by standard methods (see ref. 24 and 58 for quantification details of the total structure factor evaluation).…”
Section: Resultsmentioning
confidence: 99%
“…This study identified facilitated diffusion of N 2 between layers. On the basis of in situ neutron diffraction measurements of CO 2 adsorption on mesoporous silica, Steriotis et al attributed orientational correlations of CO 2 under confinement to vertical and lateral interactions enhanced by the large quadrupole moment of CO 2 . Cracknell et al examined rotational restrictions of CO 2 in narrow carbon pores that attract CO 2 but repulse N 2 by steric effects using GCMC to show increased selectivity of CO 2 .…”
Section: Models and Methodsmentioning
confidence: 99%
“…Since CO 2 is a more elongated molecule than N 2 , orientational correlations induced by the interaction of the quadrupoles are more evident. Samios et al [28] and Konstantakou et al [29] explored further this issue by simulating the adsorption of 'artificially' elongated CO 2 molecules, while such orientational correlations have also been observed experimentally by neutron diffraction (see [30]). Müller [16] studied CO 2 and N 2 adsorption in nanotubes and compared their angular distributions with those of hexafluorethane (C 2 F 6 ) which is an appreciably 'longer' quadrupole than CO 2 .…”
Section: Introductionmentioning
confidence: 95%